2010
DOI: 10.1007/s10995-010-0615-6
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption During Pregnancy and Risk of Placental Abruption and Placenta Previa

Abstract: The purpose of this study was to examine the association between prenatal alcohol consumption and the occurrence of placental abruption and placenta previa in a population-based sample. We used linked birth data files to conduct a retrospective cohort study of singleton deliveries in the state of Missouri during the period 1989 through 2005 (n = 1,221,310). The main outcomes of interest were placenta previa, placental abruption and a composite outcome defined as the occurrence of either or both lesions. Multiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 33 publications
2
27
0
1
Order By: Relevance
“…Placenta previa and placental abruption are both important placental pathologies. They are believed to have a similar etiology of LBW[25] and both lead to perinatal mortality and morbidity[26]. Placenta previa is a known risk factor for antepartum hemorrhage and preterm delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Placenta previa and placental abruption are both important placental pathologies. They are believed to have a similar etiology of LBW[25] and both lead to perinatal mortality and morbidity[26]. Placenta previa is a known risk factor for antepartum hemorrhage and preterm delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Articles published after the reviews have been identified through an Ovid/Medline and PsychInfo search using the keywords prenatal alcohol and pregnancy outcome and prenatal alcohol and dose, limited to English, human, and 2009 onwards. The search identified 12 papers examining low or moderate dose and fetal effects ( Table 2) [6,19,21,[87][88][89][90][91][92][93][94][95][96].…”
Section: The State Of the Evidencementioning
confidence: 99%
“…Konzumácia alkoholu počas tehotenstva je príčinou malformácií plodu, abnormalít v neurovývoji a perinatálnej úmrtnosti (21). V našej štúdií 5,5 % žien konzumovalo 3,8 ± 1,2 dl piva denne, rovnaký podiel žien konzumoval denne 1,6 ± 0,7 dl vína a 1,2 % žien konzumovalo 0,3 ± 0,0 dl destilátov denne, čo je síce pod hranicou kritickej dávky, ale konzumácia akéhokoľvek množstva alkoholu je v tehotenstve nežiaduca.…”
Section: Původní Práceunclassified